The Influence of Leadership Style and Work Stress on Work Quality Mediated by Motivation in the Regional Civil Service Agency of East Kalimantan Province - Syari, Nirmala; Riadi, Sukisno S.; Heksarini , Ariesta (Pelopor Publikasi Akademika, 2025)
The purpose of this study is to analyze and prove the influence of leadership style and work stress on motivation, to analyze and prove the influence of leadership style and work stress on work quality, to analyze and prove the influence of motivation on work quality, to analyze and prove the influence of motivation in mediating leadership style and work stress on work quality. This research was conducted at the Regional Civil Service Agency of East Kalimantan Province. The research design uses an explanatory research approach. The type of research is quantitative. The population in this study is employees of the Regional Civil Service Agency of East Kalimantan Province. The sample taken for the study was 83 respondents with a non-probability sampling method , namely by purposive sampling technique. The collection of resources was carried out by distributing questionnaires within the Regional Civil Service Agency of East Kalimantan Province. The data analysis technique used is the SEM method, namely PLS (Partial Least Square) using Smart PLS software version 4.0. The results of the study show that leadership style and work stress have a positive and significant effect on motivation, leadership style and work stress have a positive and significant effect on work quality, and motivation has a significant positive effect on work quality. In this study, it was also obtained that leadership style and work stress have a positive and significant effect on the quality of work with motivation as mediation.